Perlindungan Hak Anak dari Perilaku Orang Tua Pecandu Narkoba: Analisis Kompilasi Hukum Islam - Sari, Yopita; Zulkarnain (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study analyzes the protection of children's rights from the behavior of drug-addicted parents based on the Compilation of Islamic Law (KHI), which requires parents to care for, educate, guide, and protect children until adulthood. Using a qualitative approach with a normative legal research type, the study was conducted on primary legal sources (the Qur'an, hadith, KHI, and laws and regulations), secondary (books, journals, previous research), and tertiary. Descriptive-analytical analysis was used to examine the suitability of legal norms with child protection needs. The results of the study indicate that drug-addicted parents are unable to optimally carry out their hadhanah function, making children vulnerable to neglect, violence, and loss of education, affection, and moral and spiritual support. In such conditions, children's rights can be transferred to extended family members such as grandparents or more capable relatives, while the state is obliged to be present through legal intervention, social rehabilitation, educational services, and psychological support. Therefore, child protection requires synergy between families, communities, and the government to ensure children's rights are guaranteed. This research contributes to enriching the study of Islamic family law while providing practical recommendations in efforts to protect children affected by drug abuse by parents.